2019
DOI: 10.14202/vetworld.2019.578-583
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of extended-spectrum β-lactamase-producing Klebsiella pneumoniae isolates of chicken origin from East Java, Indonesia

Abstract: Background and Aim: Klebsiella pneumoniae is one of the respiratory disease agents in human and chicken. This bacterium is treated by antibiotic, but this treatment may trigger antibiotic resistance. Resistance gene in K. pneumoniae may be transferred to other bacteria. One of the known resistance genes is extended-spectrum β-lactamase (ESBL). This research aimed to study K. pneumoniae isolated from chicken farms in East Java, Indonesia, by observing the antibiotic resistance pattern and detect the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 22 publications
7
21
1
Order By: Relevance
“…In this research, the blaTEM gene was present in all isolates (100%; 25/25) with a 516-bp PCR product ( Fig. 3a ), as reported by Hayati et al [ 33 ].…”
Section: Resultssupporting
confidence: 84%
“…In this research, the blaTEM gene was present in all isolates (100%; 25/25) with a 516-bp PCR product ( Fig. 3a ), as reported by Hayati et al [ 33 ].…”
Section: Resultssupporting
confidence: 84%
“…It was detected with percentages of 12% in each of chicken respiratory organs and meat products and 8% in milk products. These results are higher than Hayati et al [26] )9.2 %) in Indonesia, and Hossain et al [27] (6%) and Khalda et al [28] (8.69%) in Egypt. On the contrary, our results are lower than Younis and coauthors [29] who reported that Klebsiella species were recovered from 33 out of 90 diseased chickens with an isolation rate of 36.67%.…”
Section: Discussioncontrasting
confidence: 55%
“…The pattern of antibiotic resistance is expected to be a guide in selecting the right antibiotic for treatment. The widespread use of antibiotics without close supervision can lead to antibiotic resistance (Hayati 2019). Until recently, antibiotics were easy to obtain and could be used without veterinary supervision.…”
Section: Discussionmentioning
confidence: 99%
“…Antibiotics are commonly used as therapy and to control microbial infections in humans and animals. However, the widespread use of an antibiotic may trigger the rise of antibiotic resistance not only in humans but in animals also (Kempf et al 2015;Hayati et al 2019). The European Centre for Disease Prevention and Control/ European Food Safety Authority/European Medicines Agency (ECDC/EFSA/EMA) joint report in 2014 stated that the average antibiotic consumption in animals (152 mg/kg) was higher than in humans (124 mg/kg).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation